2007
DOI: 10.1038/ng.2007.48
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis is associated with increased β-defensin genomic copy number

Abstract: Psoriasis is a common inflammatory skin disease with a strong genetic component. We analyzed the genomic copy number polymorphism of the beta-defensin region on human chromosome 8 in 179 Dutch individuals with psoriasis and 272 controls and in 319 German individuals with psoriasis and 305 controls. Comparisons in both cohorts showed a significant association between higher genomic copy number for beta-defensin genes and risk of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
509
3
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 597 publications
(535 citation statements)
references
References 15 publications
14
509
3
9
Order By: Relevance
“…41 In contrast, the increased copy number of b-defensin genes was shown to be associated with psoriasis, which is a chronic autoimmune skin disease with a prevalence of 2-3% in individuals of the European ancestry. 42,43 Apart from b-defensin genes, individuals with deletion in LCE3B and LCE3C genes of late cornified envelope (LCE) gene cluster are found to be susceptible to psoriasis. The absence of the well characterized 32 199 bp region was significantly associated (P¼1.38E À08 ) with risk of psoriasis when studied in family-based samples from Spain, The Netherlands, Italy and the United States (P¼5.4E À04 ).…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…41 In contrast, the increased copy number of b-defensin genes was shown to be associated with psoriasis, which is a chronic autoimmune skin disease with a prevalence of 2-3% in individuals of the European ancestry. 42,43 Apart from b-defensin genes, individuals with deletion in LCE3B and LCE3C genes of late cornified envelope (LCE) gene cluster are found to be susceptible to psoriasis. The absence of the well characterized 32 199 bp region was significantly associated (P¼1.38E À08 ) with risk of psoriasis when studied in family-based samples from Spain, The Netherlands, Italy and the United States (P¼5.4E À04 ).…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…These have been described as euchromatic variants (EVs) 2 (Chromosome Anomaly Collection) and involve (1) constitutional cytogenetic amplification of known CNV regions or (2) duplication, triplication or deletion of large segmentally duplicated (SD) euchromatic tracts which may include heterochromatin and accompany pseudo-dicentric variants (Table 1). Most of the EVs are clinically innocuous but the 8p23.1 EV has been associated with a number of traits [5][6][7][8] and the 4p16.1 EV co-segregated with microtia. 4 EVs need to be distinguished from pathological imbalances with which they may be similar or even identical under the light microscope.…”
Section: Introductionmentioning
confidence: 99%
“…[162][163][164][165][166] In addition, one study has shown the correlations of about 30 SNPs (that found to be associated with various traits by GWAS) with CNVs at r 2 40.5, this provides preliminary evidence of the associations and possible roles of CNVs in human complex traits. 161 The amount of evidence is expected to increase in the near future, when we have a better understanding of the characteristics of non-SNP variants and a more comprehensive map of them constructed upon the completion of the 1000 Genomes Project, and when more efficient and accurate methods are available to detect the non-SNP variants for disease-association studies.…”
Section: Non-snp Variants and Complex Diseasesmentioning
confidence: 81%